Modelling unmanned surface vehicle patrol mission with Coalition Battle Management Language (C-BML). (July 2014) - Ünal, Ömer; Topçu, Okan
Today, many military software intensive systems such as command and control systems, military simulations and decision support systems require the same military knowledge found in the operation plans and orders, which are mostly imported to the system in an application specific form. Due to the increased need for interoperability among those systems, many domain specific languages arise in order to formalize the inputs and outputs to obtain machine processable knowledge. A major domain specific language is the Coalition Battle Management Language (C-BML), which is currently under development. In this work, a scenario is developed and a coalition combat organization that has unmanned surface vehicle (USV) units under its command is created for fighting piracy. The orders and reports related to the patrol mission for the USVs are set up and modelled using C-BML. In order to model the orders, functional and temporal analyses of the actions in the orders are performed. The representativeness of the military orders, reports and requests in the scope of the scenario domain in C-BML is examined. Discussions about the expressiveness of C-BML are offered from a C-BML adopter perspective. Furthermore, we anticipate that this study will serve as a guideline for further C-BML studies.